1999
DOI: 10.1038/eye.1999.90
|View full text |Cite
|
Sign up to set email alerts
|

Role of aspirin in reducing the frequency of second eye involvement in patients with non-arteritic anterior ischaemic optic neuropathy

Abstract: Our results strongly suggest that aspirin at 325 mg/day may be effective in reducing the frequency of second eye involvement with NAION.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(36 citation statements)
references
References 15 publications
2
32
0
2
Order By: Relevance
“…7 The incidence of NAION occurring in the contralateral eye was found to vary between 24% and 48%, within a period of 5-11 years. 8 A retrospective study published in 2007 challenged the previous notion that CE-associated NAION was unrelated to prior NAION in the fellow eye. 3 The relevant study included a total 325 patients.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…7 The incidence of NAION occurring in the contralateral eye was found to vary between 24% and 48%, within a period of 5-11 years. 8 A retrospective study published in 2007 challenged the previous notion that CE-associated NAION was unrelated to prior NAION in the fellow eye. 3 The relevant study included a total 325 patients.…”
Section: Discussionmentioning
confidence: 74%
“…Aspirin could be used as a prophylactic measure in such cases at a slightly higher dose (100-325 mg/day) than usually administered on a regular basis (75 mg/ day). 8 This could prove useful especially in cases where the fellow eye needs to undergo surgery as well. In addition, susceptible individuals should be considered to undergo surgery under topical anaesthesia only, if appropriate, to eliminate the potential risk of retinal and choroidal ischaemia previously reported after periocular anaesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…It is puzzling that Stiebel-Kalish and colleagues completely ignore the findings of the two latter comprehensive studies (based on 757 unilateral NA-AION patients), which showed that aspirin has no beneficial effect 20,21 -this cannot be called "weak" evidence, and base their conclusion solely on two smaller (187 patients), comparatively poor studies. 31,32 Moreover, Salomon et al 32 (one of the two studies cited by the authors in support of their conclusion) miscited 33 the study by Beck et al 20 when advocating administration of aspirin. Beck et al 20 concluded that there is "little or no long-term (5 years) benefit in using aspirin to reduce the risk of NAION in the fellow eye.…”
Section: 12mentioning
confidence: 99%
“…Nonarteritic anterior ischemic optic neuropathy (NAION) is a devastating form of visual impairment that results from inadequate blood supply to the posterior ciliary arteries (1)(2)(3)(4)(5) . It is characterized by sudden, painless, mostly irreversible, and generally nonprogressive visual loss accompanied by nerve fiber bundle field defects, a relative afferent pupillary defect and optic disk edema (3)(4)(6)(7)(8)(9)(10)(11)(12)(13) .…”
Section: Introductionmentioning
confidence: 99%